Adversity in Aviation: Understanding Resilience in the Workplace for Female Pilots. Issue 3 (1st October 2020) - Douglas, Stephanie; Pittenger, Linda M.
ABSTRACT: Objective: This study measured the resilience of female pilots using the Connor–Davidson Resilience Scale (CD-RISC). Background: Adversity in the workplace causes occupational stress, influencing resiliency, and reducing job performance and wellness. This can lead to burnout and attrition. Female pilots in male-dominated work environments experience adversity, resulting in occupational stress. Resilience may be a mitigating factor for coping with occupational stress. Women in male-dominated professions remain the extreme minority. Further, a severe pilot shortage magnifies the need to recruit and retain pilots from underrepresented groups. Method: Exploratory and confirmatory factor analyses were applied to validate the use of the CD-RISC for measuring resilience in female pilots. Inter- and intra-group resilience score comparisons of the 1, 302 female pilots were analyzed. Results: An abridged version of the CD-RISC was found applicable to measuring resilience in female pilots. Age and work experience of the female pilots imply that they may influence higher resilience. A significantly lower resilience score was found in the sample in comparison to a national sample average resilience score. Conclusion: Female pilots' resilience is likely influenced by workplace adversity, which may lead to increased occupation stress, greater attrition, and fewer pilot entrants. Interventions aimed at increasing the resiliency of female pilots are critical to solving the pilot shortage. The findings provide insight into the recruitment, retention, and development of women in male-dominated occupations.